AKIBAT HUKUM PERCERAIAN KARENA PERPINDAHAN AGAMA (MURTAD) (STUDI KASUS PUTUSAN PENGADILAN AGAMA JAKARTA PUSAT NOMOR 25/PDT.G/2024/PA.JP) - ADINDA PRASYANTIA; WIWIN YULIANINGSIH (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Marriage is a legal bond that aims to build a harmonious family based on religious values. In practice, this goal may be disturbed when one party changes their religion after the marriage has taken place. Such a change does not automatically end the marriage, but it can become a ground for divorce if it leads to disharmony in family life. Based on normative legal research using statutory, case, and conceptual approaches, it is found that judges do not focus on the religious conversion itself, but rather on its consequences in marital life, such as ongoing conflicts, living separately, loss of communication, and failure to fulfill marital duties properly. These conditions show that the purpose of marriage can no longer be achieved, so the marriage is considered irreparable. The legal consequences include the termination of the marital bond, the end of the legal relationship between husband and wife, and court decisions regarding maintenance and child custody, which prioritize the best interests of the child. Keywords: divorce; apostasy; judicial consideration; legal consequences.